Interpersonal Communication Strengthens Web-Based Instruction - Joseph L. Donaldson; Joan S. Thomson (Journal of Applied Communications, 1999)
This study describes the interpersonal communication preferences (instructor-to-student and student-to-student) among undergraduates surveyed in a freshmen seminar in the College of Agricultural Sciences at the Pennsylvania State University. The purpose was to investigate communication preferences among students at the University Park (main) campus and three Commonwealth (branch) campuses and describe implications for World Wide Web (Web) instruction. Findings indicated significant differences between student attitudes toward student-to-student and instructor-to-student communication. With regard to success in a course, students at the Commonwealth campuses placed more importance on both student-to-student and instructor-to-student communication. The findings indicate the need for educators incorporating the Web into their curriculum to adopt a learner-centered approach to instruction, using such technology with forethought.